The prevalence and severity of teen dating violence victimization in community and at-risk adolescents in Spain - Guilera Ferré, Georgina (New directions for child and adolescent development, 2022)
The aim of the present study was to determine the prevalence and severity of teen dating violence victimization in Spanish adolescents from both community and at-risk samples. The sample comprised 1,105 community adolescents from secondary schools, 149 adolescents from child, and adolescent mental health centers, 129 from residential care centers associated with the child welfare system, and 101 from centers in the juvenile justice system. The participants, aged between 14 and 17 years, were interviewed using the Juvenile Victimization Questionnaire. The lifetime prevalence of victimization in dating relationships ranged from 2.5% to 33.7%. The prevalence of physical victimization was slightly higher in boys, while sexual and electronic victimization and injuries were more prevalent in girls. In conclusion, teen dating violence is a prevalent problem in Spain that needs to be addressed to prevent adolescents from developing risk behaviors and to avoid adverse consequences on mental health, especially in at-risk adolescents